The Victory Album : Reflections on the Good Life After the Good War. - Beidler, Philip D. (University of Alabama Press, 2010)
A vivid and penetrating history, personal and social, of growing up in post-1945 America A pervasive feeling at the end of World War II, notes Philip D. Beidler, was that Americans had "inherited the earth" and could look forward to a kind of golden age, the "Good Life after the Good War." But this good life-for all its genuine possibilities-was only accessible to some and was countered by racial tensions, the fear of communism and nuclear war, gender inequalities, and a rising consumer culture, among other problems and anxieties. In these essays-a combination of personal remembran.